PECULIARITIES OF CONDUCTING WORD FORMATION AND MORPHEME ANALYSIS IN THE RUSSIAN CLASSES AS A NATIVE (NON-NATIVE) LANGUAGE - Kukatova Olga Alekseevna, (Scholar Express Journal, 2023)
The article is devoted to topical issues of word-formation and morphemic analysis in the Russian language classes. The correct performance of both types of analyzes testifies to the student's understanding of the word-building and morphemic structure of the Russian word and the word-building system of the Russian language in general as well as the formation of spelling skills and spelling vigilance associated with the spelling of Russian suffixes and prefixes, moreover, the enrichment of the vocabulary which is necessary for productive communication in Russian language
Keywords: word formation; morphemic analysis; word formation analysis